Brand image among the purchase decision determinants - Andrianto, Novan; Fianto, Achmad Yanu Alif (Faculty of Communications Science, Dr. Soetomo University, 2020)
The purpose of this research was to measure the effect of word of mouth, perceived price, and service quality toward brand image and purchase decision. This research also aimed to measure the mediating effect of Brand Image toward the relationship between word of mouth, perceive price, and service quality with the purchase decision. This study used a survey technique that utilised questionnaires as research instruments for 200 respondents who have visited Surabaya hotels as well as Partial Least Square (PLS) data analysis techniques. The findings in this research proved that Word of Mouth, Perceived Price, and Service Quality have a significant positive effect on Brand Image and Purchase Decision. This research also revealed that brand image also has an intervening effect in the relationship of Word of Mouth, Perceived Price, and Service Quality with Purchase Decision.